Integration of Intellectual, Emotional, and Spiritual Intelligence in Improving Public Services in Sampe Cita Village - Teguh Wahyono (Yayasan Multidimensi Kreatif, 2025)
The influence of intellectual intelligence, emotional intelligence, and spiritual intelligence on the quality of public service performance in Sampe Cita Village is the main objective of this study. This study uses a quantitative approach and involves a number of respondents from village officials and communities that receive public services. Data was collected through questionnaires that aimed to measure intellectual intelligence, emotional intelligence, and spiritual intelligence, as well as people's perceptions of the quality of public service performance. To find out how much each of these three intelligence variables contributes to improving the quality of public service performance, multiple regression techniques are used to analyze the data. The results of the research are expected to improve our understanding of how important public services are at the village level to enhance intellectual, emotional, and spiritual intelligence. It is hoped that these findings will also serve as a basis for making policies and strategies to improve public services in Sampe Cita Village and other areas with similar characteristics. Since the quality of public services is one of the main indicators of the success of government at the local level, this research is important. More efficient, effective, and community-oriented public services can be made by understanding the components that affect the performance of public services.